Ynoate-Initiated Selective C–N Esterification of Tertiary Amines under Transition-Metal and Oxidant-Free Conditions - Sun, Feixiang; Feng, Huangdi; Huang, Liliang; Huang, Junhai (Synlett, 2021)
An efficient and selective method for metal- and oxidant-free deaminated esterification of tertiary amines is presented. In this protocol, ynoates play a key role to activate the Csp3–N bond through a process of in situ generation of zwitterionic salts. The transformations show that Csp3–N bond in the zwitterionic species has a lower dissociation energy than Csp2–N bond, leading to break preferentially and be trapped by carboxylic acids to generate the corresponding products in moderate to good yield.
Keywords: C–N activation; esterification; chemoselectivity; ynoate; amines